Evaluation and application of a new scintillator‐based heat‐resistant back‐scattered electron detector during heat treatment in the scanning electron microscope. (17th December 2020) - Podor, R.; Mendonça, J.; Lautru, J.; Brau, H. P.; Nogues, D.; Candeias, A.; Horodysky, P.; Kolouch, A.; Barreau, M.; Carrier, X.; Ramenatte, N.; Mathieu, S.; et al.
Abstract: A new high‐temperature detector dedicated to the collection of backscattered electrons is used in combination with heating stages up to 1050°C, in high‐vacuum and low‐vacuum modes in order to evaluate its possibilities through signal‐to‐noise ration measurements and different applications. Four examples of material transformations occurring at high temperature are herein reported: grain growth during annealing of a rolled platinum foil, recrystallisation of a multiphased alloy, oxidation of a Ni‐based alloy and complex phase transformations occurring during the annealing of an Al‐Si coated boron steel. The detector could be potentially adapted to any type of SEM and it offers good opportunities to perform high‐temperature experiments in various atmospheres.